Experimental investigation on strengthening of reinforced concrete beams using GFRP laminates. (2021) - Miruthun, G.; Vivek, D.; Remya, P.R.; Elango, K.S.; Saravanakumar, R.; Venkatraman, S.
Abstract: The objective of this paper is to study the strengthening and stiffness of concrete while using FRP laminates. Glass Fibre Reinforced Polymer (GFRP) which are taken in form of sheets and are wrapped by three methods and find out its strengthening properties. The grade of concrete of beam which is going to be used is M25. The beam is going to be undergoing flexural strength test. Again, the same ruptured beam is going to be laminated with GFRP sheets by intermittent spacing, cross over and inclined way. Then the beam is again subjected to test. Then the test results are compared between various types.